Co3O4 Hollow Polyhedrons as Bifunctional Electrocatalysts for Reduction and Evolution Reactions of Oxygen. (14th October 2016) - Dong, Duo; Liu, Yang; Li, Jinghong
Abstract : It is very important to exploit low‐cost and efficient oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) electrocatalysts for the development of renewable‐energy conversion and storage techniques. Although much attention has been made to develop efficient catalysts for ORR and OER, it is still highly desired to create new bifunctional catalysts. In this study, Co3 O4 hollow polyhedrons are synthesized as efficient bifunctional electrocatalysts for ORR and OER by simple one‐step annealing Co‐centered metal–organic frameworks (ZIF‐67). Due to the large specific surface areas and high porosity, the as‐prepared Co3 O4 hollow polyhedrons exhibit excellent electrocatalytic activities for ORR and OER in alkaline media. Co3 O4 hollow polyhedrons show higher peak current density (0.61 mA cm −2 ) with four‐electron pathway than Co3 O4 particles (0.39 mA cm −2 ), better methanol tolerance and superior durability (82.6%) than commercial Pt/C electrocatalyst (58.6%) for ORR after 25 000 s. In addition, Co3 O4 hollow polyhedrons also display excellent OER performances with smaller overpotential (536 mV) for 10 mA cm −2 than Co3 O4 particles (593 mV) and superior stability (86.5%) after 25 000 s. This facile one‐step strategy based on metal–organic frameworks self‐sacrificed templates can be used to develop the promising well‐defined porous hollow metal oxides electrode materials for energy conversion and storage technologies. Abstract : Porous hollow polyhedral Co3 O4 is synthesized by simple one‐step annealing of Co‐based metal–organic frameworks (ZIF‐67) at 300 °C in air. It shows excellent performance in both electrocatalytic oxygen reduction reaction and oxygen evolution reaction due to the large specific surface area, a high porosity to exposing more electrocatalytic active sites, and fast electron conduction with four‐electron pathway to create multiple accessible channels.